Phosphite utilization by the globally important marine diazotroph Trichodesmium. Issue 6 (23rd July 2015) - Polyviou, Despo; Hitchcock, Andrew; Baylay, Alison J.; Moore, C. Mark; Bibby, Thomas S.
Summary: Species belonging to the filamentous cyanobacterial genus T richodesmium are responsible for a significant fraction of oceanic nitrogen fixation. The availability of phosphorus (P) likely constrains the growth of T richodesmium in certain regions of the ocean. Moreover, T richodesmium species have recently been shown to play a role in an emerging oceanic phosphorus redox cycle, further highlighting the key role these microbes play in many biogeochemical processes in the contemporary ocean. Here, we show that T richodesmium erythraeum  IMS101 can grow on the reduced inorganic compound phosphite as its sole source of P. The components responsible for phosphite utilization are identified through heterologous expression of the T . erythraeum  IMS101 T ery_0365–0368 genes, encoding a putative adenosine triphosphate (ATP)‐binding cassette transporter and nicotinamide adenine dinucleotide (NAD)‐dependent dehydrogenase, in the model cyanobacteria S ynechocystis sp. PCC6803. We demonstrate that only combined expression of both the transporter and the dehydrogenase enables S ynechocystis to utilize phosphite, confirming the function of Tery_0365‐0367 as a phosphite uptake system (PtxABC) and Tery_0368 as a phosphite dehydrogenase (PtxD). Our findings suggest that reported uptake of phosphite by T richodesmium consortia in the field likely reflects an active biological process by T richodesmium . These results highlight the diversity of phosphorus sources available to T richodesmium in a resource‐limited ocean.